2013
DOI: 10.1371/journal.pone.0058027
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Inositol 1,4,5-Trisphosphate (IP3) Receptor Subtypes by Adenophostin A and Its Analogues

Abstract: Inositol 1,4,5-trisphosphate receptors (IP3R) are intracellular Ca2+ channels. Most animal cells express mixtures of the three IP3R subtypes encoded by vertebrate genomes. Adenophostin A (AdA) is the most potent naturally occurring agonist of IP3R and it shares with IP3 the essential features of all IP3R agonists, namely structures equivalent to the 4,5-bisphosphate and 6-hydroxyl of IP3. The two essential phosphate groups contribute to closure of the clam-like IP3-binding core (IBC), and thereby IP3R activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 49 publications
(64 reference statements)
0
29
0
1
Order By: Relevance
“…The slope of the Schild plots was 1.14 ± 0.41 ( n = 3) and the K D for heparin was 2.8 μg·mL −1 (pK D = 5.55 ± 0.09) (Figure 2D and Table 1). AdA has ∼10-fold higher affinity than IP 3 for all three IP 3 R subtypes (Table 1) (Rossi et al ., 2010a; Saleem et al ., 2013), and we have shown that the affinity of heparin for IP 3 R1 is similar whether IP 3 or AdA is used to evoke Ca 2+ release (Figure 1B–E). To obtain an independent measure of the affinity of IP 3 R3 for heparin, free of the problems associated with using IP 3 , we therefore repeated the Schild analysis using AdA to stimulate Ca 2+ release.…”
Section: Resultsmentioning
confidence: 67%
“…The slope of the Schild plots was 1.14 ± 0.41 ( n = 3) and the K D for heparin was 2.8 μg·mL −1 (pK D = 5.55 ± 0.09) (Figure 2D and Table 1). AdA has ∼10-fold higher affinity than IP 3 for all three IP 3 R subtypes (Table 1) (Rossi et al ., 2010a; Saleem et al ., 2013), and we have shown that the affinity of heparin for IP 3 R1 is similar whether IP 3 or AdA is used to evoke Ca 2+ release (Figure 1B–E). To obtain an independent measure of the affinity of IP 3 R3 for heparin, free of the problems associated with using IP 3 , we therefore repeated the Schild analysis using AdA to stimulate Ca 2+ release.…”
Section: Resultsmentioning
confidence: 67%
“…[245] Recent data have also focussed upon receptor subtypes in concert with adenophostin analogues. [246] Designing simple synthetic modulators of the Ins(1,4,5)P 3 receptor not based upon inositol that would mimic a myoinositol polyphosphate has always been achallenge.Since the publication of the first antagonist lead, biphenyl 2,3',4,5',6pentakisphosphate BiPh(2,3',4,5',6)P 5 ,( 262;F igure 15), [247] which also exhibits other biological activities, [248] similar compounds have been reported that explore the growing potential of benzene polyphosphates in cell-signaling applications.T hus,anoncarbohydrate/inositol phosphate Ins-(1,4,5)P 3 receptor agonist, based upon ab iphenyl structure and decorated with phosphate groups-biphenyl 3,3',4,4',5,5'hexakisphosphate (BiPh(3,3',4,4',5,5')P 6 , 263)-has been syn-…”
Section: Biphenyl Phosphate Derivativesmentioning
confidence: 99%
“…[245] Recent data have also focussed upon receptor subtypes in concert with adenophostin analogues. [246] There has always been the challenge to design simple synthetic modulators of the Ins(1,4,5)P 3 receptor not based upon inositol that would mimic a myo-inositol polyphosphate. Since the publication of the first antagonist lead, biphenyl 2,3′,4,5′,6-pentakisphosphate BiPh(2,3′,4,5′,6)P 5 , (262 in Figure 15), [247] which also exhibits other biological activities, [248] …”
Section: Biphenyl Phosphate Derivativesmentioning
confidence: 99%
“…Additionally, there has been much interest in synthetic glyconucleotides based upon the naturally occurring adenophostins, where the pharmacophore presented to the receptor is comprised of a combination of a phosphorylated carbohydrate and a pendant group that can be a nucleotide or other motif . Recent data have also focussed upon receptor subtypes in concert with adenophostin analogues …”
Section: Myo‐inositolmentioning
confidence: 99%